RARE CASE OF PRIMARY CONGENITAL GLAUCOMA WITH HYPOPLASIA CORPUS CALLOSUM - Gunawan, Prastiya Indra; Komaratih, Evelyn; ., Nurwasis; Etika, Risa; Harianto, Agus; Saharso, Darto (Journal of Ayub Medical College Abbottabad, 2018)
Primary congenital glaucoma is a rare disease that causes elevated intraocular pressure within the first three years of life. Few studies have explored the association of primary congenital glaucoma with malformation of corpus callosum. We report on a six-month-old female presenting with unilateral primary congenital glaucoma associated with hypoplasia of corpus callosum in Indonesian infant. The patient had already undergone trabeculectomy surgery. However, there no obvious improvement following the procedure given the severity of the condition. Conclusion: The failure rate of surgery in severe primary congenital glaucoma conditions is still very high, and therapy can usually preserve vision if early identification of mild or moderate form is made. Keywords: primary congenital glaucoma; hypoplasia of corpus callosum.